Avaliação “In vitro” dos extratos de basidiomicetos frente à fitopatógenos prejudiciais à produção de hortaliças de pequenos produtores da região do Baixo Amazonas - Figueiredo, Adrya da Silva (2012)
The methods used to control plant diseases have been improved in order to ensure the correct and rational use of chemicals, as well as ensure the profitability of the farmer and reduce risks to human health and the environment. Thus, biological control is in current demand and is of high importance to enable the replacement of agrochemicals. The constant concern for the environment and human health have led many researchers to investigate some alternatives aimed at reducing the use of fungicides with promising results in control of plant pathogens in several crops. The use of extracts from micro-organisms and products of their metabolism is a practice that has been extensively researched in some pathosystems. Fungi have been cited with high antifungal activity, so this work we studied aqueous extracts (hot, cold and ultrasound) and hydroalcoholic (hot and cold) and the basidiomycete Pycnoporus sanguineus and Lentinus crinitus in pathogen control, where it was shown that the extracts have significant effect on the inhibition of mycelial growth, and germination of conidia and sclerotia.